Progressive Muscle Relaxation Implementation On Anxiety Level Of Pre Op AV Shunt Surgery Patients - Fatarona, Anita; Martiana, Ina; Cahyono, Hendra Dwi; Cholida, Diana (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Chronic Kidney Disease (CKD) affects over 10% of the global population (>800 million people) and increases the risk of cardiovascular diseases such as coronary artery disease, heart failure, and stroke. One of the primary treatments for CKD is hemodialysis, with arteriovenous (AV) shunt access used in approximately 92% of procedures. AV shunt installation is a surgical procedure often associated with increased patient anxiety. In addition to pharmacological treatment, non-pharmacological approaches such as Progressive Muscle Relaxation (PMR) can be effective in reducing anxiety. This study aimed to determine the effect of PMR on the anxiety levels of patients undergoing pre-operative AV shunt installation. A quasi-experimental pretest-posttest design with a control group was used, involving 70 respondents at Jember Klinik Hospital, divided equally into intervention and control groups (n=35 each). Sampling was conducted using sequential sampling. The State-Trait Anxiety Inventory (STAI) was used to measure anxiety levels, and data were analyzed using the Wilcoxon Signed Rank Test. Results showed a significant decrease in anxiety in the intervention group after receiving PMR. The median anxiety score in the experimental group decreased from 42.66 (pre-test) to 29.57 (post-test), moving from moderate to mild anxiety. In contrast, the control group showed no significant change (pre-test median = 38.06; post-test = 40.03). The Wilcoxon test yielded a p-value of 0.000 in the intervention group, indicating a significant difference before and after the intervention. These findings support the use of PMR as an effective complementary therapy to reduce anxiety in pre-operative CKD patients undergoing AV shunt surgery.